2010
DOI: 10.1159/000318844
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of Aztreonam in Patients with Cell-Mediated Allergy to β-Lactams

Abstract: Background: Cross-reactivity between aztreonam and β-lactams is poor, but tolerability of aztreonam has been assessed in a few groups of patients suffering from IgE-mediated allergy to β-lactams. The aim of this study was to assess the cross-reactivity of aztreonam with other β-lactams and its tolerability in patients with cell-mediated allergy to these drugs. Methods: We studied 78 patients with cell-mediated allergy to β-lactams who underwent skin prick, immediate and delayed-reading intradermal tests as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
2
27
0
2
Order By: Relevance
“…The most recent study found that all penicillin-allergic patients with negative skin tests to aztreonam tolerated their administration with escalating doses [70]. Similar results have been published in patients with delayed reactions to penicillins [83].…”
Section: Aztreonam As An Alternative Treatmentsupporting
confidence: 56%
“…The most recent study found that all penicillin-allergic patients with negative skin tests to aztreonam tolerated their administration with escalating doses [70]. Similar results have been published in patients with delayed reactions to penicillins [83].…”
Section: Aztreonam As An Alternative Treatmentsupporting
confidence: 56%
“…It is less immunogenic than penicillins or cephalosporins. Patients with proven immediate and delayed sensitivity to beta-lactams have been shown to tolerate challenge with aztreonam [177][178][179] including two patients with evidence of specific IgE to aztreonam [180]. Of 45 patients with a clinical history of immediate beta-lactam, mainly penicillin allergy and positive skin or IgE tests, none had a positive intradermal test for aztreonam and all tolerated a graded intramuscular challenge [178].…”
Section: Cross-reactivity With Monobactamsmentioning
confidence: 99%
“…In a cohort of 78 patients with non-immediate allergy to beta-lactams, again mainly penicillins, and positive patch and/or delayed intradermal tests for at least one beta-lactam, none tested positive to aztreonam, and all 65 patients who underwent challenge tolerated intramuscular aztreonam [179]. However, a single case of cross-reactivity between penicillins and aztreonam has been reported in which a patient with confirmed anaphylaxis to penicillin developed anaphylaxis immediately following the administration of aztreonam [181].…”
Section: Cross-reactivity With Monobactamsmentioning
confidence: 99%
“…14,16,18,23 Specifically, the largest of these studies 18 evaluated 97 subjects with such hypersensitivity by performing both patch tests and delayed-reading skin tests with aztreonam. None of these participants had positive responses to aztreonam allergologic tests; 72 of them underwent aztreonam challenges and tolerated them.…”
Section: Reacted To Cefuroximementioning
confidence: 99%